The Effect of a Blast Load from Propane Gas Leakage on an RC Structure: A Case Study in Batna, Algeria - Tabet, M. (Engineering, Technology & Applied Science Research, 2022)
The knowledge of the way a gas explosion affects a structure is still in its development. In this study, structural analysis software was used to construct a simplified approach to predict the impact of a Dynamic Blast Load (DBL) from gas leakage. During the explosion process, the overpressure distribution in a room is decomposed to maximum dynamic pressure point (DPPmax), where the explosion damages the most the structure. The simulation of the DBL was compared with the real consequences of gas explosion with the phenomenological data of a case study in Batna, Algeria. The results show that the simulation reproduced by our modeling of the DBL at structural scale is in good agreement with a real explosion. The distribution of stresses and strains over time indicates that the gas explosion inside residential buildings affected the entire surrounding of the area of the blast.